The reality of the anxiety of sports competition and its relation to the motivation of achievement in handball players in the Asian youth Championship - المبيضين محمد; عسيلة ماجد (sports creativity, 2025)
The Reality of Sports Competition Anxiety and its Relationship to Achievement Motivation among Handball Players in the 15th Asian Youth Championship: This study aimed to identify the reality of sports competition anxiety and its relationship to achievement motivation among handball players in the Asian Youth Championship. The study sample consisted of (80) players registered for the Asian Championship from: (Jordan, Palestine, Qatar, Saudi Arabia, and Iraq). A questionnaire was used to collect data. The questionnaire consisted of (27) items on the competition anxiety scale and (20) items on the sports achievement motivation scale. The results were statistically analyzed using arithmetic means, standard deviation, one-way ANOVA, and Scheffé's test. The results showed a statistically significant correlation between the dimensions of achievement motivation, failure avoidance motivation, and anxiety. The researchers recommend the necessity of focusing on psychological guidance and counseling for players to reduce psychological pressure, especially in participation in Arab and Asian championships, and to identify the sources of psychological pressure and attempt to address them in the future.